If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6j + -2 = -7j + 7 Reorder the terms: -2 + -6j = -7j + 7 Reorder the terms: -2 + -6j = 7 + -7j Solving -2 + -6j = 7 + -7j Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '7j' to each side of the equation. -2 + -6j + 7j = 7 + -7j + 7j Combine like terms: -6j + 7j = 1j -2 + 1j = 7 + -7j + 7j Combine like terms: -7j + 7j = 0 -2 + 1j = 7 + 0 -2 + 1j = 7 Add '2' to each side of the equation. -2 + 2 + 1j = 7 + 2 Combine like terms: -2 + 2 = 0 0 + 1j = 7 + 2 1j = 7 + 2 Combine like terms: 7 + 2 = 9 1j = 9 Divide each side by '1'. j = 9 Simplifying j = 9
| -2=y-3 | | -2t+4=-t | | 4x-3(5x+7)-11=11+4(-3x-2)+2x | | -2x=y-3 | | 2(3x-3)-2(2m+4)= | | 2c+8=-7c-10 | | t^2/2t | | 175m-75+57900=61200-200 | | 9u-7=3u+5 | | 3ln(3x-4)=8 | | -3-y=1 | | -3-7=1 | | 4x^3-6=0 | | -4g=-5g-4 | | 4/5-1/5=2/5n | | 4/5-1/5=2/5 | | 2d^2-6d=10 | | (4z+6)+x+2y+106=180 | | V^2=-54 | | -3+8r=9r | | 0.2(1.2x-9)+5=9.8 | | -4d=-3d-9 | | x*0.28=1015 | | 3x^3(4x^4+172)= | | 7n^2=4n-4 | | p=5w+5l | | 8(5x)=(8*5)x | | -(-3)[(6)-(-3)]= | | -10f=-9f-8 | | 8a+12=-3+34 | | 3x^2-15=66 | | 3x^3(4x^4+172)=0 |